Primary Cutaneous Posttransplant Lymphoproliferative Disorders in Solid Organ Transplant Recipients: A Multicenter European Case Series. Issue 8 (29th May 2013) - Seçkin, D.; Barete, S.; Euvrard, S.; Francès, C.; Kanitakis, J.; Geusau, A.; del Marmol, V.; Harwood, C. A.; Proby, C. M.; Ali, I.; Güleç, A. T.; Durukan, E.; et al.
Abstract: Primary cutaneous posttransplant lymphoproliferative disorders (PTLD) are rare. This retrospective, multicenter study of 35 cases aimed to better describe this entity. Cases were (re)‐classified according to the WHO‐EORTC or the WHO 2008 classifications of lymphomas. Median interval between first transplantation and diagnosis was 85 months. Fifty‐seven percent of patients had a kidney transplant. Twenty‐four cases (68.6%) were classified as primary cutaneous T cell lymphoma (CTCL) and 11 (31.4%) as primary cutaneous B cell PTLD. Mycosis fungoides (MF) was the most common (50%) CTCL subtype. Ten (90.9%) cutaneous B cell PTLD cases were classified as EBV‐associated B cell lymphoproliferations (including one plasmablastic lymphoma and one lymphomatoid granulomatosis) and one as diffuse large B cell lymphoma, other, that was EBV‐negative. Sixteen (45.7%) patients died after a median follow‐up of 19.5 months (11 [68.8%] with CTCL [6 of whom had CD30 + lymphoproliferative disorders (LPD)] and 5 [31.2%] with cutaneous B cell PTLD. Median survival times for all patients, CTCL and cutaneous B cell PTLD subgroups were 93, 93, and 112 months, respectively. Survival rates for MF were higher than those for CD30 + LPD. The spectrum of primary CTCL in organ transplant recipients (OTR) is similar to that in the general population. The prognosis of posttransplant primary cutaneous CD30 + LPD is worse than posttransplant MF and than its counterpart in the immunocompetent population. EBV‐associated cutaneous B cell LPD predominates in OTR. Abstract : This case series suggests that primary cutaneous posttransplant lymphoproliferative disorders of T cell origin are more common than those of B cell origin, the spectrum of primary cutaneous T cell lymphoma in organ transplant recipients is similar to that in the general population, the prognosis of posttransplant primary cutaneous CD30+ lymphoproliferative disorders is worse than its counterpart in the immunocompetent population, and EBV‐associated cutaneous B cell lymphoproliferative disorders predominate in organ transplant recipients.